Pengaruh Penambahan Lobak Dan Brokoli Terhadap Tingkat Kesukaan Nugget Bandeng Sebagai Alternatif Snack Penderita Hipertensi - Ahmad Alwi; Asrul Bahar; Rita Ismawati; Choirul Anna Nur Afifah (Lembaga Pengembangan Kinerja Dosen, 2023)
Hypertension is a condition where a person's blood pressure increases above normal which can inhibit the work of the heart. Strategies that can be used to reduce the incidence of hypertension is to utilize products favored by the public that have the potential to lower blood pressure. Food ingredients such as milkfish, white radish, and broccoli. All three have the opportunity to be processed into food products that are well known among the public, efficient, practical, and acceptable to all circles where the product is Nugget. This study aims to determine the effect of adding white radish and broccoli to the preference level of milkfish nuggets as an alternative snack for hypertensive patients. This study used an experimental design, namely RAL with 6 treatments. The treatment was factor L as the addition of white radish with 3 levels and factor B as the addition of broccoli with 2 levels. The results showed that the milkfish nuggets with the addition of 70% white radish and 30% broccoli were preferred by the panelists with a protein nutrient content of 9.48% using the Kjeldahl test, 16.4% fat using the Weibull test, 0.18% potassium using the ASS, 2.24% sodium using the ASS test, and 248.98 kcal energy using calculations.